Impact of transformational leadership on work performance, burnout and social loafing: A mediation model - Hira Khan; Maryam Rehmat; Tahira Hassan Butt; Saira Farooqi; Javaria Asim (Future Business Journal, 2020)
The aim of this research was to study the effect of transformational leadership on employees' work outcomes which include their work performances and working burnout, and their working behavior such as social loafing at workplace. Also, it studies the impact of intrinsic motivation as a mediator between transformational leadership and other stated variables. A cross-sectional survey was conducted to collect data from 308 employees working in the telecommunication sector. To test the hypotheses, Model 4 of Process Hayes was used to test direct and mediating effects among transformational leadership and employees' work outcomes and working behavior. The results showed that transformational leadership has a significant positive relationship with mediator intrinsic motivation. The results also concluded that work performance has positive significant relationship with transformational leadership. However, there is indirect and insignificant relationship of transformational leadership with working burnout and social loafing. Therefore, it can be stated that organizational leaders must have transformational attributes by getting informed of their employees well because transformational leader can inspire employees to achieve anticipated or significant outcomes. It gives employees self-confidence over specific jobs, as well as the power to make decisions once they have been trained.
Keywords: 650; Intrinsic motivation; Social loafing; Transformational leadership; Work performance; Working burnout